C‐peptide levels in pediatric type 2 diabetes in the Pediatric Diabetes Consortium T2D Clinic Registry. Issue 4 (5th May 2015) - Gregg, Brigid; Connor, Crystal G.; Cheng, Peiyao; Ruedy, Katrina J.; Beck, Roy W.; Kollman, Craig; Schatz, Desmond; Cengiz, Eda; Tamborlane, William V.; Klingensmith, Georgeanna J.; Lee, Joyce M.; ,
Abstract: Objective: To describe C‐peptide levels in a large cohort of children with type 2 diabetes T2D and examine associations with demographic and clinical factors. Methods: The Pediatric Diabetes Consortium (PDC) T2D Registry has collected clinical and biologic data from youth with T2D cared for at eight US Pediatric Diabetes Centers. In this study, we assessed C‐peptide levels in 331 youth with T2D (mean age, 16.1 ± 2.5 yr; median T2D duration, 2.4 yr). Results: Median (interquartile range) for 90 fasted C‐peptide measurements was 3.5 ng/mL (2.3–4.8 ng/mL) [1.2 nmol/L (0.8–1.6 nmol/L)] and for 241 random non‐fasted C‐peptide measurements were 4.2 ng/mL (2.6–7.0 ng/mL) [1.4 nmol/L (0.9–2.3 nmol/L)]. C‐peptide levels were lower with insulin therapy (p < 0.001), lower body mass index (p < 0.001), hemoglobin A1c (HbA1c) ≥9% (p < 0.001), and T2D duration ≥ 6 yr (p = 0.04). Among those with duration ≥6 yr being treated with insulin and with a HbA1c level ≥9.0% (75 mmol/L), 75% of the fasted and 80% of the non‐fasted C‐peptide values were above 0.2 nmol/L. Conclusions: In youth with T2D, a decline in C‐peptide is associated with deterioration of metabolic control and the need for insulin treatment. C‐peptide levels decrease over time. However, even insulin‐treated patients with 6 or more years of T2D and elevated HbA1c levels retain substantial endogenous insulin secretion.